STRATEGY OF SALES AND COMMUNICATION OF HOTEL SERVICES DURING THE WAR - Mariia Kulyk; Margaryta Boiko; Myroslava Bosovska; Alla Okhrimenko (Agora International Journal of Economical Sciences (AIJES), 2023)
In the conditions that have developed in the economy of Ukraine, the organization of processes in the hotel business and the formation of sales and communication strategies have undergone changes, as well as the tourism sector as a whole. Each hotel enterprise needs to clearly understand the plan of actions and decisions to ensure the correct operation of the enterprise, adapted to external changes. The purpose of the article is to study the essence and tasks of forming a strategy of sales and communication of hotel services during the war, studying the main aspects. After February 24, 2022, most Ukrainian businesses and enterprises, in particular hotels and restaurants, faced uncertainty and confusion about what to do next. The tourist flow came to a sudden halt along with air and rail connections. A significant number of workers lost the opportunity to be present at workplaces or went abroad. Due to the hostilities, the offer on the hotel market of Ukraine has decreased. The objective of survey providing in the study is the determination of regional trends in the development of the hotel market of Ukraine during the war and understanding the peculiarities of marketing strategies that affect the involvement of new hotel product consumers' segments through the booking channels and the formation of a positive image of hotels. Methods of generalization, analysis and synthesis, comparison, scientific abstraction and systematization were used to fulfil the set tasks and achieve the main goal of the research of strategy of sales and communication of hotel services during the war.
Keywords: 330